Automatic fiscal policies to combat recessions - Seidman, Laurence S. (Armonk, N.Y. : M.E. Sharpe, 2003)
Offers fiscal policy options that can complement automatic stabilizers and counter-cyclical monetary policy to combat recessions. It argues for an independent fiscal policy board or the Federal Reserve to decide changes in the magnitude of Congress' fiscal policy package of stimulus or restraint.
Includes bibliographical references (p. 219-222) and index.
gau 16/06/14; opc 09/01/17
Loans
Keywords: Income tax; Fiscal policy; Taxation; United States